Does Federalism Lead to Excessively High Taxes? - Keen, Michael J; Kotsogiannis, Christos (American Economic Review, 2002)
The relative strengths of vertical and horizontal tax externalities turn on the balance between the interest responsiveness of the supply of savings and demand for capital, the extent to which immobile factors are taxed by the states, and the strength of preferences between federal and state expenditures. The vertical externality will dominate if the aggregate tax base of the federation is responsible to the state tax instrument. Tax interactions in federations are more complex than has often been supposed.